2002
DOI: 10.1152/jn.2002.87.6.2946
|View full text |Cite
|
Sign up to set email alerts
|

Collicular Microstimulation During Passive Rotation Does Not Generate Fixed Gaze Shifts

Abstract: crostimulation during passive rotation does not generate fixed gaze shifts. J Neurophysiol 87: 2946 -2963, 2002; 10.1152/jn.00675.2001. We investigated whether saccades evoked by electrical stimulation (E-saccades) in the superior colliculus can compensate for passive sinusoidal head rotation in yaw so as to keep the rapid gaze shift constant. After accounting for variations in E-saccade onset position, we found significant horizontal metric changes, proportional to head velocity, in 31 of 37 experiments in 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Here, we demonstrated that saccade behavior was modulated by pupil size adjusted to the level of global luminance, and pupillary luminance responses affected both pro‐ and anti‐saccade behavior. Many of saccade decisions, in the real‐world situation, are made when other important factors, for example, vestibular signals, are not well‐controlled (Rincon‐Gonzalez et al., 2016; Van Beuzekom & Van Gisbergen, 2002a, 2002b). Future research that explores the interactive processes between the oculomotor and other systems is thus important to advance our knowledge of eye movement control in the real world.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we demonstrated that saccade behavior was modulated by pupil size adjusted to the level of global luminance, and pupillary luminance responses affected both pro‐ and anti‐saccade behavior. Many of saccade decisions, in the real‐world situation, are made when other important factors, for example, vestibular signals, are not well‐controlled (Rincon‐Gonzalez et al., 2016; Van Beuzekom & Van Gisbergen, 2002a, 2002b). Future research that explores the interactive processes between the oculomotor and other systems is thus important to advance our knowledge of eye movement control in the real world.…”
Section: Resultsmentioning
confidence: 99%
“…While the vertical component of the voluntary saccade was typically correct, the horizontal component was compromised, and biased in the direction of the quick phase. The same authors also tested how oblique saccades induced by electrical microstimulation in the monkey superior colliculus (SC) are modified by concurrent sinusoidal yaw rotation (Van Beuzekom and Van Gisbergen 2002b). Again, results showed a kinematic effect only on the horizontal component of the induced saccade, not the vertical component.…”
Section: Discussionmentioning
confidence: 99%